Impact of Military Service in Vietnam on Coping and Health Behaviors of Aging Veterans During the COVID-19 Pandemic - Stellman, Jeanne M.; Stellman, Steven D.; Spiro, Avron; Pless Kaiser, Anica; Smith, Brian N. (Frontiers in Public Health, 2022)
Many Vietnam War veterans who experienced military trauma still exhibit PTSD symptomatology. Little is known about how new stressful situations, like the COVID-19 pandemic, affect previously traumatized people or whether they will react differently to them. We explore whether military combat experiences in Vietnam affect veterans’ perceived abilities to cope with the COVID-19 and whether current PTSD symptoms and later-adulthood reengagement with trauma memories are related to coping. We examine the extent that current PTSD symptoms and trauma reengagement relate to preventive practices. Participants were part of a randomly sampled cohort of American Legionnaires who responded to two previous surveys (1984, 1998), were born 1945-1953 and deployed to Vietnam 1963-1973, thus representing an aging veteran population. A survey supplement assessed coping with the pandemic and adherence to public health guidelines. The response rate was 74% (N=507); 422 (61.6%) completed the COVID-19 supplement. Military experiences were found to affect coping with 41.4% reporting they affected ability to cope with COVID-19. Medium- and high-combat veterans were more likely to report that military experience affected coping than low-combat (OR 2.4, 95% CI 1.51-3.96; 2.6, 95% CI 1.41-4.61, respectively). Those with high PTSD scores had 7.7-fold (95% CI 4.3-13.17) increased likelihood of reporting that their coping was affected, compared to low-PTSD scorers. Few adopted social distancing (4%), staying at home (17%), or ceasing usual activities (32%); high-combat veterans were least likely to stay home. Veterans who practiced handwashing, sanitizer use, mask-wearing, and surface disinfection had significantly higher PTSD scores than those who did not. Veterans with higher scores on the LOSS-SF scale associated more reengagement with trauma memories and were more likely to engage in personal preventive strategies. Analysis of open-ended responses supported these findings. We conclude that fifty years after returning from Vietnam, PTSD scores were high for high-combat veterans, suggestive of PTSD diagnosis. Military experiences affected coping with COVID both positively and negatively, and may have helped instill useful personal health behaviors. Veterans, especially those with PTSD symptomatology, may have special needs during stressful times, like the COVID-19 pandemic, affecting compliance with recommended practices, as well as their overall health and well-being.